(untitled) (International Journal of Health, Animal Science and Food Safety, 2018)
The objective of this study was to investigate the effect of feeding broiler chicken on different vegetable oils with commercial multi- enzyme feed additives on the quality characteristics of chicken burger. A total of 216 one-day-old chicks of (Hubbard) strain were randomly assigned to six dietary treatments as (2×3) factorial designs where two sources of dietary oil contained soybean oil and palm oil with three levels of commercial multi-enzyme feed additives. Treatments were: soybean oil only (T1), soybean oil+ ZAD (T2), soybean oil+ AmPhi-BACT (T3), palm oil only (T4) , palm oil + ZAD (T5) and palm oil + AmPhi- BACT (T6). Results showed that chicken burger of T1 group had the higher pH value (6.22); slight difference was found in pH value of T3 group (6.18). No significant difference was found in burger of T5 and T6 group. Burger processed from T1 group had the higher T.B.A value (0.115) followed by burger of T5 (0.076); while the lowest T.B.A value found in burger of T2 group (0.031). No significant differences were found in shrinkage measurements. Burger processed from T6 group had the higher score of sensory attributes and overall acceptability, while the differences between the other burger groups were not significant.